Knowledge Sharing Practices on Work-Related Issues among Managerial Group in Private Organizations - Khaddraa, Rajuli (Universiti Malaysia Sarawak (UNIMAS), 2018)
The purpose of this study is to explore knowledge sharing practices in the organization. In order to get an in-depth understanding about the practice, various aspects related to knowledge sharing such as its contributing factors, barriers, methods and approaches that can help promote, the benefits, with whom knowledge is shared, types of knowledge shared as well as the characteristics of the knowledge sharer were studied. A qualitative method that is in an open-ended and structured questionnaire was used to collect data, followed by one or more interview with the subject matter, if further clarification is needed. A total of twentythree informants, of executive and manager level from different private organizations in Malaysia were involved in this study. The conceptual analysis highlights various themes derived from the obtained data. The contributing factors of knowledge sharing and its inhibitors emerged similarly as previous studies. They include issues related to individual, institutional, relationship and knowledge. Meanwhile, the barriers consist of issues related to individual, institutional and technology. In addition, the benefits of knowledge sharing also supported previous studies linking knowledge sharing with innovation, performance and learning. On the other hand, the activities that promotes knowledge sharing in the organization ranges from written documentation, verbal communication, information technology tools and other organizational events or practices. The popular social platformFacebook and Whatsapp applications were also found to assist employees in sharing knowledge freely. Other than that, the majority of informants consider conscientiousness as the top attribute of the knowledge sharer. Furthermore, there are two types of knowledge identified in this study, which informants were willing to share. They include tacit and explicit knowledge. On with whom to share knowledge, it was reported that knowledge was v not only disseminated within and between firms, but was also dependent on the characteristics of knowledge recipients whom perceived by the knowledge contributors as competent, have good attitude and willingness, inquirer, and rightful or relevant. In the relational analysis, several relationships between the informants’ demographic background and knowledge sharing variables were found. Above all, the study also contributes toward the body of knowledge as well as policies, methodologies, practices, society and directions for future research.